Extreme population structure and high interspecific divergence of the Silene Y chromosome. - Ironside, J; Filatov, D (2005)
Previous studies have demonstrated that the diversity of Y-linked genes is substantially lower than that of their X-linked homologs in the plant Silene latifolia. This difference has been attributed to selective sweeps, Muller's ratchet, and background selection, processes that are predicted to severely affect the evolution of the nonrecombining Y chromosome. We studied the DNA diversity of a noncoding region of the homologous genes DD44Y and DD44X, sampling S. latifolia populations from a wide geographical area and also including the closely related species S. dioica, S. diclinis, and S. heuffelii. On the Y chromosome of S. latifolia, we found substantial DNA diversity. Geographical population structure was far higher than on the X chromosome and differentiation between the species was also higher for the Y than for the X chromosome. Our findings indicate that the loss of genetic diversity on the Y chromosome in Silene occurs within local populations rather than within entire species. These results are compatible with background selection, Muller's ratchet, and local selective sweeps, but not with species-wide selective sweeps. The higher interspecific divergence of DD44Y, compared to DD44X, supports the hypothesis that Y chromosome differentiation between incipient species precedes reproductive isolation of the entire genome, forming an early stage in the process of speciation.